Overlapping Map Penggunaan Overlapping Map dari Hasil Pengerjaan Reading Comprehension pada Aplikasi Viat – Map - Zahri, Riris Silvia; Andoko, Banni Satria; Amalia, Eka Larasati (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 1 (2023): JNATIA Vol. 2, No. 1, November 2023DO - 10.24843/JNATIA.2023.v02.i01.p01, 2023)
The development of learning with technology continues to grow rapidly. Learning English especially Reading Comprehension in learning English for students is quite a big challenge. Viat-map is a web-based application that implements the Toulmin Argument concept for use in English Reading Comprehension subject. User acceptance of the Viat-Map application is one of the factors that supports the continued use of the application. Measurement of user acceptance of the Viat-Map application is carried out using the TAM (Technology Acceptance Model) method. This study aims to evaluate the implementation of the Viat-Map application using the TAM method, so that user perceptions and the factors that influence users in using the application can be identified. The research method uses a questionnaire as a tool to collect data on 26 users of the Viat-Map application. The results showed that user acceptance of the Viat-Map application had a positive effect on 3 TAM variables, namely perceived user convenience 89.56%, perceived usefulness 86.68%, and technology acceptance 81.87%. This shows that application developers can focus on improving development on the Viat-Map application acceptance variable because the percentage variable value is smaller than the other variable values. Keywords : Toulmin Argument, Viat-Map, Technology Acceptance Model